2018
DOI: 10.1111/1753-0407.12625
|View full text |Cite
|
Sign up to set email alerts
|

Association between smoking and glycemic control in diabetic patients: Results from the Risk Evaluation of cAncers in Chinese diabeTic Individuals: A lONgitudinal (REACTION) study

Abstract: Active smoking is a modifiable risk factor for poor glycemic control in Chinese diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 35 publications
5
25
0
2
Order By: Relevance
“…On the other hand, the odds of poor glycemic control was four times higher among smokers compared to nonsmokers. This complies with previous study that reported current smokers had an increased risk of poor glycemic control [60]. As well as Willi C et al reported that the risk of diabetes is shown to be higher by 45% in smokers than among nonsmokers [61].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the odds of poor glycemic control was four times higher among smokers compared to nonsmokers. This complies with previous study that reported current smokers had an increased risk of poor glycemic control [60]. As well as Willi C et al reported that the risk of diabetes is shown to be higher by 45% in smokers than among nonsmokers [61].…”
Section: Discussionsupporting
confidence: 92%
“…In another cohort study of 10,551 men and 15,297 Chinese women with DM, smoking was associated with an increased risk OR of 1.49 in men and 1.56 in women for poor glycemic control (defined as HbA1c ≥ 7.0%), particularly in elderly patients [84]. The relationship is dose-dependent and independent of traditional confounding factors, including sociodemographic and lifestyle factors.…”
Section: Smoking and Glycemic Controlmentioning
confidence: 99%
“…We used the GATK HaplotypeCaller (v4.0.4.0) to call variants per sample and produced an intermediate file in GVCF format and consolidated GVCF files from 10,588 samples into one GVCF file using the GATK CombineGVCFs (v4.0.4.0). When we combined the GVCF files, the low-complexity regions (LCRs, covering 2% of the genome and identified by the mDust program) 63 were ignored. Based on the combined GVCF file, the joint call was performed using the GATK GenotypeGVCFs (v4.0.4.0) with filter of the GATK Variant Filtration (v4.0.4.0).…”
Section: Methodsmentioning
confidence: 99%
“…The measurement and collection of phenotype information for all individuals are described previously. 14 , 16 , 63 Before genotype-phenotype association analyses, all variants were subjected to a series of quality control with criteria: (1) median depth > 8; (2) within LCRs (< 7 single base repeat units); (3) homozygous variants (AF ≥ 0.90); (4) homozygous variants (AF ≥ 0.2); (5) genotyping rate ≥ 90%; (6) HWE > 0.000001. 4,764,593 SNPs passed the quality control.…”
Section: Methodsmentioning
confidence: 99%